Biomarcadores en espondiloartropatías (2010)
Among rheumatic diseases and specifically spondyloarthropathies (SpA), the study of biomarkers, defined as molecules that reflect either biologic or specific pathological process, is an important and necessary area in basic and clinical research, being a consequence or the response of an intervention. Other markers provide information about the pathogenesis of this disease. Recently, HLA-B27 has been used as diagnostic criteria to detect SpA. Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) are clinical scores used to assess disease activity. A new activity index, Ankylosing Spondylitis Disease Activity Score (ASDAS) considers erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) as biomarkers. This review describes the state of the art of research on SpA biomarkers. There are promising new candidates as biomarkers such as metallopro-teinase 3, Type II collagen neoepitopes (C2C and C1-2C), C-propeptide of Type II collagen (CPII), aggrecan 846 epitope, macrophage colony stimulating factor, serum amyloid A protein and interleukin-6, among others.